The Freest Country in the World East Germany's Final Year in Culture and Memory - Brockmann, Stephen (Columbia, MD Boydell & Brewer, Incorporated, 2023)
AcknowledgmentsIntroduction: The Memory of Freedom1: Protocols of History: Reunification Documentaries from 1989/19902: Anarchy in the GDR3: The National Liberation Zone4: Coming of Age as the State Dies: Three Novels and Their Heroes5: Provincial Theater: Fiction Film Struggles to Address German Reunification in the Early 1990s6: The Grand Theater of the East and the Imaginary Stasi: The Emergence of the Standard Depiction of German Reunification in Film and on Television7: Ritual, Repetition, and Memory: Commemorating and Memorializing 1989/1990Conclusion: The Last GDRSelected Works CitedFilmographyIndex
E-Book / Zugriff nur im Lesesaal